Generalized Twisted Kloosterman Sum Over ℤ[i] - Varbanets, S. P. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
The twisted Kloosterman sums over Z were studied by V. Bykovsky, A.Vinogradov, N. Kuznetsov, R. W. Bruggeman, R. J. Miatello, I. Pacharoni, A. Knightly, and C. Li. In our paper, we obtain similar estimates for K χ (α, β; γ; q) over ℤ[i] and improve the estimates obtained for the sums of this kind with Dirichlet character χ (mod q 1), where q 1 | q.